Research of the strategic prospects for development of Ukraine integration into the global system of international trade - Бабенко, Віталіна Олексіївна; Петухова, Віолетта Олегівна; Сідоров, Михайло Вадимович (Technology audit and production reserves, 2016)
Strategic forecasting method has disadvantages because it can become ineffective with fluctuations in market conditions, socio-economic instability of member states of international economic organizations, the deepening global financial crisis and the resulting decline in international trade between countries. Disadvantages may be addressing through the deepening of strategic forecasting in subsequent studies based on trade and economic disparities. The contents and a list of basic trade-economic features of countries that form the basis for comparative and further detailed economic analyzes of Ukraine’s foreign integration policy in the global system of international trade are considered. The performance is improved, which reflects the level of trade and economic development. It is not only reflects the state of trade and economic relations, but also to characterize the foreign policy that is aimed at integration into the international integration space. The equation for the forecast of growth curves for defined indicators is obtained that makes it possible to find comparative assessment of countries in the process of global integration in dynamics and develop predictive scenarios of the member countries of integration processes in the long-term period. These indicators also allow determining a single integrated indicator that shows the condition of integration process and evaluate the potential for their development. Methodical maintenance of definition of the strategic positioning of major trading partners of Ukraine is performed on the basis of definition of integral index, based on forecast trends in the development of integration processes in the field of foreign trade and identifying the most promising ones. Based on the forecast scenarios of development for Ukraine and countries that are major trading partners of Ukraine, priority scenarios of their integration into the global system of international trade are specified. Theoretical logic and quantitative analysis of the strategic positioning for three promising forecast periods gives recommendations on areas of foreign policy priorities of Ukraine and the development of integration in the field of trade and economic relations with member states of international integration associations.